(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This paper explores innovative pedagogical approaches for developing critical thinking among university students in English language instruction. In today’s globalized academic environment, English serves not only as a medium of communication but also as a means of intellectual engagement and analytical inquiry. The study examines how critical thinking can be systematically integrated into English language curricula through interactive, student-centered methodologies. The research highlights the significance of reflective learning, problem-based tasks, and digital learning tools as mechanisms to foster independent reasoning and creativity. Findings suggest that implementing such approaches enhances students’ cognitive flexibility, academic performance, and lifelong learning competence.